2013
DOI: 10.1371/journal.pone.0069407
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transcription Factor mRNAs in Identified Oxytocin and Vasopressin Magnocellular Neurons Isolated by Laser Capture Microdissection

Abstract: The oxytocin (Oxt) and vasopressin (Avp) magnocellular neurons (MCNs) in the hypothalamus are the only neuronal phenotypes that are present in the supraoptic nucleus (SON), and are characterized by their robust and selective expression of either the Oxt or Avp genes. In this paper, we take advantage of the differential expression of these neuropeptide genes to identify and isolate these two individual phenotypes from the rat SON by laser capture microdissection (LCM), and to analyze the differential expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…The brain block containing the hypothalamus was then rapidly frozen on dry ice and stored at −80°C until sectioning was done. Details about this procedure were previously published [ 28 , 29 ]. Briefly, the frozen brain was mounted onto Tissue-Tek OCT compound (Sakura Finetek USA, Torrance, CA) on a chuck with the caudal portion of the brain placed down on the chuck, and the brain on the chuck was placed in the cryostat (Reichert-Jung 2800, Frigocut, Heidelberg, Germany) for twenty minutes to equilibrate the brain with a chamber temperature (CT) of −20°C and an object temperature (OT) of −16°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain block containing the hypothalamus was then rapidly frozen on dry ice and stored at −80°C until sectioning was done. Details about this procedure were previously published [ 28 , 29 ]. Briefly, the frozen brain was mounted onto Tissue-Tek OCT compound (Sakura Finetek USA, Torrance, CA) on a chuck with the caudal portion of the brain placed down on the chuck, and the brain on the chuck was placed in the cryostat (Reichert-Jung 2800, Frigocut, Heidelberg, Germany) for twenty minutes to equilibrate the brain with a chamber temperature (CT) of −20°C and an object temperature (OT) of −16°C.…”
Section: Methodsmentioning
confidence: 99%
“…# LCM0211). The PEN membrane frame slide was loaded on the instrument with the tissue side down and a clean glass slide underneath it acting as support [ 28 ]. The rat SON is completely visualized in the 20X objective view of the Arcturus XT LCM microscope which allowed for the microdissections of multiple SONs from many serial sections from the same brain specimen onto the same cap.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Chu and Zingg showed that a mouse OXT gene promoter transfected into Neuro 2A was activated by ROR α, a member of the ROR/RZR orphan receptor subfamily, produced a six‐fold increase in transcription at two sites (−160 bp and −180 bp) in the CHRE region. In a recent study from our laboratory that investigated whether ROR α was present in the SON, we found that ROR α was indeed significantly present in MCNs but at higher levels in AVP‐MCNs than OXT‐MCNs . Another NHR present in the SON is oestrogen receptor β and, interestingly, its expression is also normally greater in AVP‐MCNs than in OXT‐MCNs and is inversely correlated with the level of expression of the neuropeptide genes .…”
Section: Discussionmentioning
confidence: 81%
“…Laser-capture microdissection has been used in a variety of publications for the identification of marker genes that may help in the genetic dissection of functionally well characterized regions of the medial hypothalamus (Segal et al, 2005; Paulsen et al, 2009; Landmann et al, 2012; Lee et al, 2012; Humerick et al, 2013). …”
Section: Discussionmentioning
confidence: 99%